PROTECTION OF CRYPTOCURRENCIES: CURRENT CHALLENGES AND PROSPECTS FOR DEVELOPMENT - PASHORIN, VALERIY; YAROVOY, ROMAN; ZAKHARENKOV, DMYTRO; MYLASHENKO, VIKTOR (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article investigates the issues of implementing mechanisms for ensuring the security of cryptocurrency generation, storage and transmission. The author shows the main directions of solving the problem of protecting digital currency from possible fraudulent actions during transactions and its storage in electronic wallets. The essence of the mechanisms for ensuring the security of the Bitcoin cryptocurrency is revealed. The main problems of cryptocurrency protection related to hacker attacks and fraud, security of electronic wallets and vulnerabilities of smart contracts are identified. It is noted that despite the use of advanced cryptographic methods, cryptocurrencies remain a target for hackers. The ECDSA algorithm with proven cryptographic strength is used to generate electronic wallet keys. The use of the peer-to-peer architecture of a network of distributed ledger nodes and blockchain technology in the cryptocurrency payment system significantly increases the level of security of cryptocurrency use. The fundamental differences between cryptocurrencies and digital currencies are presented. The properties of cryptographic hash functions used to protect transactions from possible falsification or substitution of transaction blocks of the electronic registry are determined.A shortened algorithm for generating an electronic wallet address is presented. Recommendations are made to improve protection mechanisms against new types of attacks, develop more efficient hashing algorithms, and improve the usability of electronic wallets. The author also emphasizes the importance of developing and implementing security standards for cryptocurrencies, which will facilitate their widespread use and integration into financial systems.
Keywords: digital currency; cryptosystem; blockchain; bitcoin; hash function; electronic wallet